Evaluation of Snake Venom’s PhospholipaseA2 Enzyme Inhibition Activity of Cyphostemma adenocoule - Kaushik, Atul; Tesfai, Teamrat S.; Barkh, Daniel K.; Ghebremeskel, Furtuna K.; Zerihun, Habtom G.; Woldeab, Saron W. (Current Chemical Biology, 2020)
Background: A snake bite is fundamentally an injury often resulting in puncture wounds meted out by the animal's fangs and occasionally resulting in envenomation. Rate of snake bites around 5,400,000 bites per year leads to over 2,500,000 envenomings and around 125,000 fatal cases annually. Snake venom enzymes are rich in metalloproteinases, phospholipaseA2, proteinases, acetylcholinesterases and hyaluronidases. Objective: Cyphostemma adenocoule is traditionally being used for the treatment of snake bites in Eritrea. The present research was aimed at evaluating the snake venom enzyme inhibition activity of C. adenocoule against puff adder venom and developing a base for the traditional use of the plant against snakebites in Eritrea. Methods: The anti-venom activity of C. adenocoule was assessed in-vitro through phospholipaseA2 enzyme inhibition assay using egg yolk as a cell. The ethanol and chloroform extracts of C. adenocoule showed in vitro anti phospholipase A2 activity, whereas the water extracts of the plant showed no activity. Results: Among the extracts of C. adenocoule, the highest percentage of inhibition was obtained from chloroform extract (95.55% at 100mg/ml). The extract showed prominent activity at different concentrations (34.7% at10mg/ml, 48.8% at 20mg/ml, 54.8% at 40mg/ml, 60.9% at 60mg/ml, 80.5% at 80mg /ml). The ethanol extract also showed certain activity at various concentrations (25.22% at10mg/ml, 14.78% at 20mg/ml, 2.6% at40mg/ml). The activity of the chloroform extracts increases as concentration increases, whereas the activity of the ethanol extracts decreases as concentration increases. The aqueous extract of C. adenocoule did not show any activity at all concentrations. Conclusion: In this study, the chloroform and ethanol extracts of the plant inhibited the enzyme of interest and thus proved the efficacy of anti-snake venom activity of the plant.
Keywords: Cyphostema adenocoule